KESESUAIAN PENYIMPANAN OBAT HIGH ALERT DI INSTALASI FARMASI RSD IDAMAN BANJARBARU - Mochammad Maulidie Alfiannor Saputera; Rakhmadhan Niah; Pebryanti Puspita Rini; Ayu Soraya (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
High alert drugs are drugs that have the risk of causing great harm to patients if management is inappropriate. The high alert drug group is divided into 3 namely High Concentrated Electrolytes, Look Alike Sound Alike (LASA) and cytostatic. The purpose of this study was to determine the percentage of suitability of storage of each high alert drug (LASA & High Concentrate Electrolyte) based on the Standard Operating Procedure (SOP) of the ideal hospital. This research is a descriptive study, data collected by using observation sheets made by researchers based on SOP of Idaman Banjarbaru Hospital. The population and sample of this study are all high alert drugs in the Pharmacy Installation at Idaman Banjarbaru Hospital. The results of the study found that the overall percentage of suitability of high alert drug storage based on the SOP of Idaman Banjarbaru Hospital in the 4 units of the Pharmacy Installation Service at Idaman Banjarbaru Hospital was 83.48% accordingly. Each group described a high alert drug that is 95% High Concentrated Electrolyte which is appropriate, LASA as much as 67.95% which is appropriate, and High alert (other than the LASA and High Concentrated Electrolyte class) as much as 82.50% appropriate.